Investigation of different concentrations of MS media effects on gene expression and steviol glycosides accumulation in Stevia rebaudiana Bertoni - Kahrizi, Danial; Ghaheri, Matin; Yari, Zahra; Yari, Khirollah; Bahraminejad, Sohbat (Cellular and Molecular Biology, 2018)
Stevia rebaudiana Bertoni is one of two species that contains steviol glycosides. Among steviol glycosides that extracted from leaves, stevioside and rebaudioside A are the two major and the sweetest glycosides that are about 200-300 times sweeter than sucrose with zero calories. The best method for stevia propagation is tissue culture. So, for investigation of nutrients in medium, we studied the effect of different concentrations of MS media (MS, 0.5 MS, 0.25 MS, 0 MS) on morphological traits, UGT74G1 and UGT76G1 genes expression and accumulation of steviol glycosides in stevia leaves. The best growth rate (0.472 mm/d) has occurred in plants grown in MS media. Also, the highest gene expression of UGT74G1 gene (1.000 Total lab unit) was seen under MS treatment. However, the highest expression level of UGT76G1 gene (1.701 Total lab unit) was observed at plants grown in 0 MS. The highest amount of both Stevioside and Rebaudioside A (14.23 and 8.12, respectively) were accumulated in plants under MS treatment. Obviously, dilution of MS media associated with decreasing in both expression of the intended genes and accumulation of steviol glycosides.